The behavior over time of postnatal depression symptomatology and its early detection via the Edinburgh Postnatal Depression Scale: An Italian longitudinal study - Cattaneo, Maria Caterina; Roveraro, Sara; Chiorino, Valentina; Macchi, Elena Alessandra; Salerno, Roberta; Gatti, Monica; Arcaro, Laura; Barretta, Francesco; Fontana, Camilla Barbara; Colombo, Lorenzo; Rossi, Piero Giorgio; Mosca, Fabio (International Journal of Advanced Nursing Studies, 2015)
Background: Becoming a mother for the first time is a significant developmental transition and postpartum mood disorders represents the most frequent form of maternal morbidity following delivery.Objective: To investigate the ability of Edinburgh Postnatal Depression Scale (EPDS) to detect, in the first days postpartum, mothers at risk of developing depressive symptomatology over time.Results: The percentage of mothers with an EPDS score ≥10 decreases over time: 23.77% at 2/5 days postpartum, 15.57% at 2 months and 9.02% at 6 months after delivery. Among mothers with a depressive symptomatology after 2/5 days postpartum, 41.38% maintained an EPDS score ≥10 at 2 months too, while 20.69% of them manifested depressive symptoms at 6 months as well. Both correlation and linear regression showed a significant association between EPDS scores in all three administrations of the study but EPDS score at 2/5 days postpartum is more associated and predictive to maternal mood at two months than at six months postpartum.Method: A longitudinal study was conducting on 122 primiparous mothers who filled out EPDS and a General Information Questionnaire at 2/5 days postpartum, at 2/3 and 6/7 months after delivery. Women with high EPDS scores (≥10) were compared to those who had scored <10 in all the three steps and longitudinal analysis were conducted.Conclusion: Implementing EPDS in the first week postpartum allows identifying women at high risk to maintain depressive symptoms over time. These findings could be useful for health care interventions after delivery and for researchers involved in the study of transcultural aspects of postnatal depression.